THE ISSUE OF CULTURE ON HOSPITALITY STUDENTS IN LANGUAGE ACQUISITION - Anggayana, I Wayan Agus (Akademi Komunitas MAPINDO, 2022)
This study aims to find the relationship between language acquisition and culture and its changes for hospitality students. The instruments used in this research are (a) daily notes, (b) an interview guide, and (c) a camera. Observation methods, interview techniques and documentation in the form of recorded speech results when conducting research. The subordinate relationship reflects a quality of the relationship that is only one-sided, meaning that cultural dynamics affect the dynamics of language acquisition for hospitality students. It is evidenced by the relationship that states language is the result of culture when compared to the language used by hotel students with Balinese in general. It is partly influenced by foreign tourists who often communicate with hospitality students, where the students practice and do internships. It can sharpen knowledge linguistically in language learning. Keywords: Hospitality Student, Language Acquisition, Culture, Linguistics.